Effect of Multiple Substitutions (Pb, Ti, Zr) on Structural, Permittivity and Electrical Properties of BiFeO3 Ceramics (JOURNAL OF ADVANCES IN PHYSICS, 2017)
Three complex polycrystalline samples of Bi1-xPbxFe1-x Zrx-yTiyO3,with the combination of (i) x, y = 0.0 (BFO), (ii) x = 0.5 and y = 0.5 (BFPTO)and (iii) x = 0.5 and y = 0.25 (BFPZTO) were prepared by a standard mixed oxide (solid state reaction route) method at optimized calcinations (900oC) and sintering (930-950oC)temperatures. The effect of multiple (Pb, Ti and/or Zr) substitutions of different amount onthe permittivity, impedance and modulus characteristics of the materials has been investigated at different frequencies and temperature. Limitation associated with BiFeO3 (BFO) due to its semiconducting behavior acts as constraint in polling the material at room temperature leading to large dielectric loss. Attempts were made to minimizethe loss by substitution of Pb on the Bi site and Ti and/or Zr at the Fe site of BFO. The study indicates that the phase transition temperature of BFO is lowered,the degree of diffuse phase transition is enhanced and electrical parameters (dielectric constant, electrical resistivity, remnant polarization and maximum polarization) areincreased with a significant reduction in dielectric loss as a consequence of the substitution. Detailed studies of Nyquist plots with impedance and electric modulus data suggest that the existence of non-Debye type of relaxation phenomena in the materials. The ac conductivity study reveals that the conduction mechanism in the material obeys universal Jonschers power law.